Miconazole for the treatment of vulvovaginal candidiasis. In vitro, in vivo and clinical results. Review of the literature - Pedro Antonio Regidor; Manopchai Thamkhantho; Chenchit Chayachinda; Santiago Palacios (Taylor & Francis Group, 2023)
At concentrations achieved following systemic administration, the primary effect of imidazoles and triazoles on fungi is inhibition of 14-α-sterol demethylase, a microsomal cytochrome P450 (CYP) enzyme. Imidazoles and triazoles impair the biosynthesis of ergosterol for the cytoplasmic membrane and lead to the accumulation of 14-α-methyl sterols. The synthetic imidazole miconazole is additionally able to increase intracellular reactive oxygen species, at least in part through inhibition of fungal catalase and peroxidase. This unique feature of miconazole is probably the basis for its fungicidal activity in C. albicans, in addition to the fungistatic mode of action. Studies show that miconazole is superior to nystatin treatment and demonstrate its impact as one of the best options in managing vulvovaginal candidiasis. Regarding recurrent vulvovaginal candidiasis, several new drugs are currently developed to ensure effective treatment also for this group of patients.